The Analysis of Black People’s Psyche: A Brief study on Afro-American Folktales (International Journal of Food and Nutritional Sciences, 2022)
This research article examines the representation of Afro-American folktales and its role in the lives of enslaved Black people who regained their self-identity with the help of written narratives. In the Postcolonial Literature, they have intrigued researchers because these tales reveal the concealed history and lost traditions of Afro-Americans during the enslavement era. The purpose of writing this article is to examine how White Americans controlled and overshadowed the cultural beliefs of Afro-Americans through manipulating their mind forcefully. Since, White people belonged to the ruling class they dehumanized black people. They controlled their life which caused a sense of fear and lack of confidence in them. Through this research article my main aim is to analyse the deep and psychological meaning Afro-American folktales that explore slavery, gender oppression, class conflicts and other social taboos faced by enslaved black people.